PEMETAAN PERMASALAHAN KRIMINALITAS PADA ANAK: ANAK BERMASALAH DENGAN HUKUM DI KOTA TOMOHON PROVINSI SULAWESI UTARA - Sartiah Yusran; Ulfa Matoka (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
This study was conducted to seek answer questions relating to child criminal chases among others: (i) criminal forms of what children do and what causes it, (ii) what are the problems faced by children with problems of law ranging from arrest, litigation and while in prison,; (3) the rights of children who are in prison based on Law No. 12 of 1995 on Corrections and also about the protection of Children Act No. 23 of 2002. The purposes of this study were: (1) to describe the forms of crimes commited by children, the causes of violations of law, and family background; (2) an inventory of child problematic legal issues ranging from the arrest and trial process; (3) an inventory of child problematic legal issues while in prison (problem: clothing, food, rooms, health, education, psychological, safety, recreation, access to information, and so on); (4) to reveal the fulfillment of the rights of Children who have a legal trouble that stayed in prison accordance with Law No. 12 of 1995 on Correctional and the Law on Child Protection No. 23 of 2002 that have been fulfilled or not. The research respondents were 21 as residents of Tomohon prison under 18 years old. The case that brought them to prison, generally consist six kinds of cases. The case categorized as severe, moderate, and mild. The Severe cases murder, rape, and stabbing. Molestation was categorized medium, while the light cases were theft and fights. Not all law cases especially mild cases ended with immurement, but they were placed on daycare for a while. There were some problems faced by children during in prison: (1) lack of prison facilities to support the development of children, especially in terms of education, health, and skills; (2) there was physical violence that commited by officer such as kicked and slapped, (3) as well as sexual harassment form the officer toward the child. This study concluded that the main causes of child law problem in Tomohon prison were; fights, molestation, murder, stabbing, woman or rape, and theft. During detention, children with problems of law were not comprehensive and less sensitive. The growth of children towards positive still questionable. Therefore, the expected involvement of all parties or all stakeholders for handling legal problems of children in a comprehensive and sensitive, so that they can help in a positive growth, both intellectual and emotional intelligence as well as their life skills.